Exploration for Byproduct Critical Element Resources: Proxy Development Using a LA–ICP–MS Database - McNulty, Brian A.; Jowitt, Simon M. (Frontiers in Earth Science, 2022)
The transition to low- and zero-CO2 energy generation, storage and transport will require a range of metals that are often considered critical and are produced as byproducts. The reliance of some critical elements on the production of main metal commodities like Cu and Ni, is a significant source of supply risk. However, how can we evaluate resource scarcity and supply risks for elements that we do not routinely analyze for and characterize in present day mined ores? Here we demonstrate a method for exploring for and assessing the byproduct critical element potential of magmatic sulfide and volcanogenic massive sulfide deposits using an LA-ICP-MS database. The results indicate potential for significant enrichments of Sb, Bi, Cd, Co, Se and Te in pentlandite (Ni sulfide), chalcopyrite (Cu sulfide) and sphalerite (Zn sulfide), demonstrating the need for a holistic approach to critical element research with byproducts having the potential to solve perceived resource scarcity challenges.